Severe cicatricial entropion repair using mucous membrane graft in Stevens–Johnson syndrome - Bolajoko Adewara; Swati Singh (Indian Journal of Ophthalmology, 2022)
Background: Severe cicatricial entropion in Stevens–Johnson syndrome (SJS) patients is difficult to treat and is associated with a higher recurrence rate. Also, entropion in the presence of lid margin mucous membrane graft (MMG) further complicates the surgical anatomy and approach. Purpose: To report a modified surgical technique of repairing severe upper eyelid cicatricial entropion in an SJS patient with history of lid margin MMG. Synopsis: Cicatricial entropion in patients with SJS is entirely different from trachomatous cicatricial entropion. The involvement of the lid margin with keratinization, tarsal scarring, persistent conjunctival inflammation, and unhealthy ocular surface affects the surgical approach and outcomes. Conjunctiva-sparing surgery with reconstruction of the lid margin using MMG, flattening and repositioning the anterior lamella, and covering the bare tarsus with MMG rather than leaving it raw are the necessary modifications in this technique from conventional anterior lamellar recession. The video demonstrates the surgical technique for harvesting and preparation of a labial MMG, the splitting of the anterior and posterior lamella of the lid margin, scar tissue release between the lash line and the tarsus, repositioning of the anterior lamella, and anchoring of the labial MMG. Highlights: Anterior lamellar recession combined with MMG wrapping the lid margin and bare tarsus offers good cicatricial entropion repair outcomes. Removal of fat and submucosa from the mucosal graft should be done for better cosmesis. Adequate separation of the scar tissues from the lash line and the tarsus is essential. Video link: https://youtu.be/6HsKgeZQCyY